2018
DOI: 10.3390/w10111577
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Public Flood Risk Perception in a Flood-Prone City: The Case of Jingdezhen City in China

Abstract: Understanding and improving public flood risk perception is conducive to the implementation of effective flood risk management and disaster reduction policies. In the flood-prone city of Jingdezhen, flood disaster is one of the most destructive natural hazards to impact the society and economy. However, few studies have been attempted to focus on public flood risk perception in the small and medium-size city in China, like Jingdezhen. Therefore, the purpose of this study was to investigate the public flood ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 52 publications
5
63
2
1
Order By: Relevance
“…In Cologne, self-protective manners by residents of urban areas prone to floods helped in reducing the economic cost of floods by about 80% [24]. In Jingdezhen city in China, only 13.8% of the participants of a study held that the public should also be responsible for flood protection [17]. In the north of Italy, 60% of study participants felt willing to adopt some behaviors for reducing their vulnerability to floods or landslides [13].…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Cologne, self-protective manners by residents of urban areas prone to floods helped in reducing the economic cost of floods by about 80% [24]. In Jingdezhen city in China, only 13.8% of the participants of a study held that the public should also be responsible for flood protection [17]. In the north of Italy, 60% of study participants felt willing to adopt some behaviors for reducing their vulnerability to floods or landslides [13].…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…However, the study neither asked the residents their perceived causes of floods nor their preferred methods of disaster risk communication. In Jingdezhen City (China), Wang et al [17] found that previous flood knowledge and experience, and trust in government significantly influenced public perception of flood risks but did not investigate whether the respondents were willing to participate in risk mitigation activities in the event of a disaster. As such, the present research contributes to filling these knowledge gaps and builds on the literature using the following methods.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The second one is the mutual aid behaviors among residents in the communities during flood emergency evacuation. According to the results of our several field investigations and questionnaire surveys in Jingdezhen, Jiangxi Province, China, it was found that during flood emergency evacuation, residents generally had the consciousness and behaviors of helping each other and going to shelter together [1]. Moreover, the behaviors of helping each other to evacuate to the shelter together can be motivated, encouraged by the local government.…”
Section: Introductionmentioning
confidence: 98%
“…Flood disasters are a major threat to human society and economic systems, and they can easily wipe out the wealth accumulated in the past [1]. In recent years, the frequency and scope of flood disasters have increased significantly as well as the economic losses and human casualties caused by floods (https://www.cred.be).…”
Section: Introductionmentioning
confidence: 99%